2023
DOI: 10.3390/ijms241914871
|View full text |Cite
|
Sign up to set email alerts
|

Efferocytosis and Respiratory Disease

Wenxue Zheng,
Zhengjie Zhou,
Xiaoping Guo
et al.

Abstract: Cells are the smallest units that make up living organisms, which constantly undergo the processes of proliferation, differentiation, senescence and death. Dead cells need to be removed in time to maintain the homeostasis of the organism and keep it healthy. This process is called efferocytosis. If the process fails, this may cause different types of diseases. More and more evidence suggests that a faulty efferocytosis process is closely related to the pathological processes of respiratory diseases. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 148 publications
0
2
0
Order By: Relevance
“…During ALI, there is significant death of epithelial and endothelial cells. Activated neutrophils have an extended lifespan, but they eventually undergo apoptosis ( 139 ). Phagocytosis of apoptotic cells is termed efferocytosis.…”
Section: Endocytic Pathways In the Setting Of Ali/ardsmentioning
confidence: 99%
See 1 more Smart Citation
“…During ALI, there is significant death of epithelial and endothelial cells. Activated neutrophils have an extended lifespan, but they eventually undergo apoptosis ( 139 ). Phagocytosis of apoptotic cells is termed efferocytosis.…”
Section: Endocytic Pathways In the Setting Of Ali/ardsmentioning
confidence: 99%
“…Phagocytosis of apoptotic cells is termed efferocytosis. It has been shown, that efferocytosis plays a critical role in the resolution of inflammation in the setting of ALI ( 139 , 140 ). Of note, a recent clinical study demonstrated that patients with ARDS exhibit impaired alveolar macrophage efferocytosis ( 140 ).…”
Section: Endocytic Pathways In the Setting Of Ali/ardsmentioning
confidence: 99%